Fumarate Hydratase-Deficient Renal Cell Carcinoma—A Clinicopathological Study of a Series of 11 Cases - Aswathy A. Menon; Swapnil Rane; Uma Sakhadeo; Gagan Prakash; Amit Joshi; Mahendra Pal; Amandeep Arora; Nilesh Sable; Aparna Katdare; Palak Popat; Priyamvada Maitre; Archi Agarwal; et al. (Indian Journal of Medical and Paediatric Oncology)
Introduction Fumarate hydratase (FH)-deficient renal cell carcinoma (RCC) is a rare, molecularly defined renal tumor with aggressive behavior. The diagnosis of these tumors is challenging because of varied morphology and limited access to molecular testing and immunohistochemistry (IHC) for FH and 2-succinocysteine. We aim to elucidate the histomorphology, clinical presentation, and follow-up of this tumor in this first series of cases of FH-deficient RCCs from India.